Heavy Metal Assessment in Water and Sediments at Jaikwadi Dam (Godavari River) Maharashtra, India - Patil, Satish S; Kaushik, Geetanjali (International Journal of Environment, 2016)
The indiscriminate release of industrial effluents, domestic sewage, agricultural runoff have resulted in extensive contamination of water and soil with heavy metals thereby causing hazard to flora and fauna and the aquatic ecosystem. Therefore, there is a need for biological monitoring studies to evaluate the toxic concentrations of various chemical compounds so that certain preventive measure can be taken to ensure the safety of the environment. Therefore, this study was focused at investigating few of the important heavy metals like zinc, chromium, cadmium, mercury and lead, in water along with sediments of the Jaikwadi dam. It has been found that the content of mercury was the highest in both water (15.24 - 18.21 μg/L) and sediments, it is followed by lead (14.31 - 18.38 μg/L), cadmium (1.95 - 2.29 μg/L), chromium (0.68 - 4.00 μg/L) and finally zinc (0.88 - 1.77 μg/L). High concentrations particularly of mercury and lead warrant studies for their remediation so that the concentration remains safe for the populace dependent on the water.INTERNATIONAL JOURNAL OF ENVIRONMENTVolume-5, Issue-2, March-May 2016, Page: 75-88